Can Adult Care Diminish the Effects of Friends' Assaultive Behaviors on Bullying Perpetration among African American Youth?. Issue 2 (7th February 2020) - Hong, Jun Sung; Song, EunJee; Llorent, Vicente J.; Patel, Sadiq; Voisin, Dexter R.
ABSTRACT: The aim of the present study is to explore whether caring relationships with parents and teachers might buffer the effects of friends' assaultive behavior on bullying perpetration among urban African American adolescents. The study sample comprised 483 African American adolescents, 12–19 years of age, in Chicago's Southside. Hierarchical multivariate regression analyses were conducted to explore the direct and indirect effects of parental care, parental monitoring, and teacher care, on the association between friends' assaultive behavior and bullying perpetration. The findings suggest no direct association between parental care, parental monitoring, and bullying perpetration. However, higher level of teacher care was related to lower level of bullying perpetration. Additionally, an interaction term, teacher care × friends' assaultive behavior was found to be associated with lower bullying perpetration. Implications for practice and research are discussed.